2023
DOI: 10.3390/en16041846
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Building Materials: Embodied Energy and Embodied Carbon of Masonry

Abstract: The growing attention to sustainability and life cycle issues by European and international policies has recently encouraged the adoption, in the construction sector, of environmental labels able to quantify the impacts on environment associated with the fabrication of several building materials, e.g., their embodied energy and carbon. Within this framework, since walls represent a large percentage of building mass and therefore of embodied impacts, this article collects and analyzes nearly 180 Environmental P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Therefore, the selection process could be objective, subjective, or both. Nevertheless, the environmental impact of this choice can be significant from an LCA viewpoint (Tokede et al, 2023) and should be driven by sustainability (Asdrubali et al, 2023). Janjua (2021) recently reported that a complex relationship exists between the service life of materials and buildings, which has another relationship with the environmental performance of a building.…”
Section: Service Life Of Building Materials and Recurrent Embodied En...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the selection process could be objective, subjective, or both. Nevertheless, the environmental impact of this choice can be significant from an LCA viewpoint (Tokede et al, 2023) and should be driven by sustainability (Asdrubali et al, 2023). Janjua (2021) recently reported that a complex relationship exists between the service life of materials and buildings, which has another relationship with the environmental performance of a building.…”
Section: Service Life Of Building Materials and Recurrent Embodied En...mentioning
confidence: 99%
“…Nevertheless, the environmental impact of this choice can be significant from an LCA viewpoint (Tokede et al. , 2023) and should be driven by sustainability (Asdrubali et al. , 2023).…”
Section: Building Materials and Energymentioning
confidence: 99%
“…Understanding this inverse tendency is critical for weighing the benefits and drawbacks of increasing compressive strength vs. increasing embedded carbon content. The increased cement consumption necessary for greater strength combinations adds to the environmental effect, emphasizing the importance of a balanced strategy that takes into account both strength needs and sustainability goals [68].…”
Section: Relationship Between Compressive Strength and Embodied Carbo...mentioning
confidence: 99%
“…This material, used since ancient times, represents an energy-efficient resource with almost zero embodied energy—less than 0.5 MJ/kg (7.8 MJ/kg for Portland cement) [ 24 , 25 , 26 , 27 , 28 ]. This significant disparity underscores the potential of earthen construction to mitigate the overall environmental footprint of buildings.…”
Section: Introductionmentioning
confidence: 99%